The Male Gaze in Margaret Atwood's "I Dream of Zenia with the Bright Red Teeth" - Silventoinen, Henna (My University, 2025)
This thesis examines the male gaze, which is a term coined by Laura Mulvey, in relation to feminist author Margaret Atwood’s short story “I Dream of Zenia with the Bright Red Teeth”. The ways in which the male gaze shows itself in the story are explained and the motives behind them are theorised. The aim of my research is to illustrate the different shapes in which the male gaze exists in this piece of literature as well as the intentions behind Atwood’s narrative choices regarding the character of Zenia. I intend to aid in filling a gap in research by connecting the male gaze theory to this short story by Atwood. This thesis ultimately concludes that the male gaze is present in Atwood’s story in many forms, but more importantly it is used as a narrative tool in the process of critiquing larger patriarchal structures of society. The need for research on feminist issues and the male gaze persists, and this thesis intends to partake in these important conversations.
Keywords: the male gaze, feminism, objectification, feminine stereotypes, literary theory